Palestine-Israel journal of politics, economicss and culture (Jerusalem Palestine-Israel journal of politics, Economics and Culture, 1994)
The Palestine-Israel Journal provides background material and in-depth analysis of various aspects of the conflict from the perspective of both sides, thus helping to shed light on the complex issues dividing Israelis and Palestinians and the relationship between the two peoples
Keywords: Political situation; POLITICAL CONDITIONS; ECONOMIC CONDITIONS; PALESTINIANS; GAZA STRIP; WEST BANK; ARAB-ISRAELI CONFLICT